Hubungan Kebijakan Pajak dengan Kepatuhan dan Inovasi: Tinjauan Literatur Sistematis - Sunaryo, Deni; Lestari, Etty Puji; Puryandani, Siti; Hersugondo, Hersugondo ("LAWSUIT" Jurnal Perpajakan, 2024)
Background: Tax is an important instrument to support national development and socio-economic development. Tax reform is often used to improve efficiency, innovation, and taxpayer compliance. However, the effectiveness of this policy is often hampered by the complexity of the tax system, weak law enforcement, and negative public perceptions of government spending. Objective: This article aims to conduct a systematic analysis of the recent scientific literature discussing the relationship between tax policy, taxpayer compliance, and innovation, taking into account socio-cultural factors such as gender. Methods: The study was conducted by analyzing 10 scientific articles from databases such as Scopus, Taylor & Francis, and Elsevier. Articles were selected based on inclusion criteria covering the themes of tax compliance, corporate innovation, and socio-economic impacts of tax reform. Results: The main findings show that corporate tax rate reforms positively contribute to innovation, while taxpayer compliance behavior is influenced by social factors such as gender. However, weak enforcement capacity in developing countries hampers the effectiveness of these reforms. Conclusion: Integration of digital technology and data-driven approaches is needed to improve tax compliance and the effectiveness of tax policies in various countries.